CONEXÕES MATEMÁTICAS NO ESTUDO DE SUCESSÕES NUMÉRICAS NA FORMAÇÃO DE PROFESSORES: CAMINHOS PARA UMA APRENDIZAGEM SIGNIFICATIVA - Bortoli, Marcelo de Freitas (2022)
Taking into account that mathematical connections are present in the teaching and learning processes, this work explores the relationship between those connections and meaningful learning. Thus, through the mathematical connections, especially those within Mathematics, this research aims foremost to analyze how the mathematical connections regarding patterns, regularities and numeric sequences made by final year students of Teacher Training Courses contributed to the development of meaningful learning of Arithmetic Sequences of Higher Order. To do such, we used the Meaningful Learning theoretical basis proposed by David Ausubel, as well as the connections, one of the five standards of teaching and learning process presented by the National Council of Teachers of Mathematics (NCTM). This is qualitative research with a content analysis approach and its data was collected from remote classes, during synchronous sessions, through the application of the Potentially Meaningful Teaching Unit (PMTU) for teaching patterns, regularities and numeric sequences. The work was conducted with eight students of a Teacher Training Course at a governmental university in the state of Paraná. The literature review was based on books, papers, master’s thesis and doctoral dissertations about mathematical connections, meaningful teaching and learning and teacher formation, as well as the analysis of current legislation for Elementary and Superior Education. The results show that the students reflected on their previous knowledge, that is possible to produce instructional material through mathematical connections and that the mathematical interconnection is a valuable guiding principle for teaching practices.